The adversities of a monarchical frontier policy. The scales of fraud around the “Real Situado” of Chile, 1670-168 - Cerón, Elisa (Revista Complutense de Historia de América, 2024)
In 1602, after the so-called “Curalaba disaster” in 1598, the monarchy established a subsidy to support the army of the kingdom of Chile settled on the Bío-bío frontier. This annual subsidy of 212,000 maravedíes, called situado real, lasted throughout the 17th century and part of the 18th century. However, during the second half of the 17th century there was a progressive increase in complaints from governors, officials and the army due to the continuous problems surrounding the arrival of the situado to Chile. Fraud and corruption on various scales, the insufficiency of the Lima treasury for the remittance of the situado, as well of the shipments themselves were just some of the problems that the Crown tried to control. The purpose of this article is to analyze the period prior to the royal decree of 1687, investigating the various erosions suffered by the Real Situado through three levels of analysis: viceroyalty, governorship and local spheres. We propose that the corruption committed by various actors was the main cause of the loss of the wealth that was sent from the treasury in Lima. Based on the study of administrative documentation we propose that the fraud committed by actors at different levels was the main cause of the loss of the resources that were sent from the royal treasury in Lima.
Keywords: Real Situado; Fraud; Corruption; Viceroyalty of Perú; Chile; 17th century